The Educational System and the Ethnic Skills Gap among the Working-Age Population: An Analysis of 16 Western Immigration Countries. (June 2020) - Heisig, Jan Paul; Schaeffer, Merlin
Research shows that children of immigrants, the "second generation, " have comparatively high educational aspirations. This "immigrant optimism" translates into ambitious educational choices, given the second generation's level of academic performance. Choice-driven (comprehensive) education systems, which allow the children of immigrants to follow their ambitions, are therefore regarded as facilitating their structural integration. The authors focus on an underappreciated consequence of these findings. If the second generation strives for higher qualifications than children of native-born parents with similar performance, working-age children of immigrants should have lower skills than children of native-born parents with comparable formal education. This could result in (statistical) employer discrimination and ultimately hamper integration. This pattern should be particularly pronounced in choice-driven education systems and in systems that emphasize vocational education. Two-step regression models using data on 16 countries support these expectations. The authors explore implications of these findings for comparative research on ethnic gaps in labor market attainment.